Detection of Significant Coronary Artery Disease by Noninvasive Anatomical and Functional Imaging. (March 2015) - Neglia, Danilo; Rovai, Daniele; Caselli, Chiara; Pietila, Mikko; Teresinska, Anna; Aguadé-Bruix, Santiago; Pizzi, Maria Nazarena; Todiere, Giancarlo; Gimelli, Alessia; Schroeder, Stephen; Drosch, Tanja; Poddighe, Rosa; et al.
Abstract : Background—: The choice of imaging techniques in patients with suspected coronary artery disease (CAD) varies between countries, regions, and hospitals. This prospective, multicenter, comparative effectiveness study was designed to assess the relative accuracy of commonly used imaging techniques for identifying patients with significant CAD. Methods and Results—: A total of 475 patients with stable chest pain and intermediate likelihood of CAD underwent coronary computed tomographic angiography and stress myocardial perfusion imaging by single photon emission computed tomography or positron emission tomography, and ventricular wall motion imaging by stress echocardiography or cardiac magnetic resonance. If ≥1 test was abnormal, patients underwent invasive coronary angiography. Significant CAD was defined by invasive coronary angiography as >50% stenosis of the left main stem, >70% stenosis in a major coronary vessel, or 30% to 70% stenosis with fractional flow reserve ⩽0.8. Significant CAD was present in 29% of patients. In a patient-based analysis, coronary computed tomographic angiography had the highest diagnostic accuracy, the area under the receiver operating characteristics curve being 0.91 (95% confidence interval, 0.88–0.94), sensitivity being 91%, and specificity being 92%. Myocardial perfusion imaging had good diagnostic accuracy (area under the curve, 0.74; confidence interval, 0.69–0.78), sensitivity 74%, and specificity 73%. Wall motion imaging had similar accuracy (area under the curve, 0.70; confidence interval, 0.65–0.75) but lower sensitivity (49%, P <0.001) and higher specificity (92%, P <0.001). The diagnostic accuracy of myocardial perfusion imaging and wall motion imaging were lower than that of coronary computed tomographic angiography ( P <0.001). Conclusions—: In a multicenter European population of patients with stable chest pain and low prevalence of CAD, coronary computed tomographic angiography is more accurate than noninvasive functional testing for detecting significant CAD defined invasively. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00979199. Abstract : Supplemental Digital Content is available in the text.